1998
DOI: 10.1073/pnas.95.26.15831
|View full text |Cite
|
Sign up to set email alerts
|

Origin of a chloroplast protein importer

Abstract: During evolution, chloroplasts have relinquished the majority of their genes to the nucleus. The products of transferred genes are imported into the organelle with the help of an import machinery that is distributed across the inner and outer plastid membranes. The evolutionary origin of this machinery is puzzling because, in the putative predecessors, the cyanobacteria, the outer two membranes, the plasma membrane, and the lipopolysaccharide layer lack a functionally similar protein import system. A 75-kDa pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 45 publications
6
94
1
Order By: Relevance
“…Interestingly, Hmp35 is also predicted to be a predominantly ␤-structured protein with a 47% ␤-sheet content, which is comparable with the 45% predicted and the 48 -52% determined experimentally for MspA (53). The Toc75 protein translocase found in chloroplasts likewise exists as a ␤-barrel (54). Furthermore, the ␤-barrel structure is found in all outer membrane proteins in Gramnegative bacteria and a large number of outer membrane proteins in organelles of symbiotic origin, mitochondria, and chloroplasts.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, Hmp35 is also predicted to be a predominantly ␤-structured protein with a 47% ␤-sheet content, which is comparable with the 45% predicted and the 48 -52% determined experimentally for MspA (53). The Toc75 protein translocase found in chloroplasts likewise exists as a ␤-barrel (54). Furthermore, the ␤-barrel structure is found in all outer membrane proteins in Gramnegative bacteria and a large number of outer membrane proteins in organelles of symbiotic origin, mitochondria, and chloroplasts.…”
Section: Discussionsupporting
confidence: 59%
“…However, no convincing evidence for multimer formation has been obtained for either ShlB or FhaC, thus contrasting with eukaryotic Omp85-like proteins (15, 16). These findings have led others to suggest that the tetrameric Omp85 protein translocation system in eukaryotes may have evolved from more primitive, monomeric bacterial Omp85 homologs (3,5).…”
mentioning
confidence: 99%
“…However, no convincing evidence for multimer formation has been obtained for either ShlB or FhaC, thus contrasting with eukaryotic Omp85-like proteins (15, 16). These findings have led others to suggest that the tetrameric Omp85 protein translocation system in eukaryotes may have evolved from more primitive, monomeric bacterial Omp85 homologs (3,5).In this study, we examined Haemophilus influenzae HMW1B, an OM protein that has been demonstrated to be critical for the secretion of the H. influenzae HMW1 adhesin across the OM and is considered to be a member of the TPS pathway, like ShlB and FhaC (12,17). We found that HMW1B exhibits heat-modifiable mobility, a hallmark of ␤-barrel proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because homologs exist in extant cyanobacteria (one of which was shown to be essential for viability), these proteins are postulated to be derived from a common ancestor in the original endosymbiont (Bö lter et al, 1998;Reumann et al, 1999Reumann et al, , 2005. Detailed phylogenetic analyses suggested that Toc75 and OEP80 diverged early in the evolution of chloroplasts (Inoue and Potter, 2004).…”
mentioning
confidence: 99%